Aplikasi Server Data PDC Terpadu dan Terpusat pada Laboratorium Menggunakan Server Linux (Studi Kasus pada Universitas Dian Nuswantoro Semarang) - Arif Sulistiyo (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2005)
Linux is an Operating System, which acts as a communication service between the hardware (or physicalequipment of a computer) and the software (or applications which use the hardware) of a computer syste.Networking support in Linux is advanced and superior to most other Operating Systems. Since the peopledeveloping Linux collaborated and used the Internet for their development efforts, networking support cameearly in Linux development. As an Internet server, Linux is a very good choice, often outperforming WindowsNT, Novell and most UNIX systems on the same hardware (even multiprocessor boxes). Linux is frequentlychosen by leading businesses for superior server and network performance. This section covers server-sidedetails of building and configuring a PDC (Primary Domain Controller) using Samba.When building andconfiguring the PDC it is important to pay attention to details.Linux supports all of the most common Internetprotocols, including Electronic Mail, Usenet News, Gopher, Telnet, Web, FTP, Talk, POP, NTP, IRC, NFS,DNS, NIS, SNMP, Kerberos, WAIS and many more. Linux can operate as a client or as a server for all of theabove and has already been widely used and tested. Linux also fits easily and tightly into Local Area Networks(LANs), regardless of system combinations, providing full and seamless support for Macintosh, DOS, Windows,Windows NT, Windows 95, Novell, OS/2, using their own native communication protocols. Linux can do all ofthis with low memory requirementsKeywords: Linux, Operating Systems, PDC.